The Use of Electronic Money as a Transaction System in Indonesia - Abidin, Rachmat; Dewi, Sofia; Asmalasari, Ai Siti; Syawali, Fikri Ikhsan; Hidayat, Hilmi Sirojuddin (Journal of Islamic Economics and Business, 2023)
Advancements in technology during the 4.0 era promise significant benefits for human civilization. This study focuses on the technological evolution of digital payment methods, specifically electronic money (e-money), in Indonesia's digital economy landscape. E-money, utilizing electronic devices like chips or servers, serves as a cashless payment alternative, contributing to a notable decline in cash usage. The proliferation of e-money is evident in Indonesia, driven by startups and competition among key players like Gojek, OVO, and Shopee. The research employs qualitative methods, including a descriptive approach and literature survey, drawing insights from various sources such as books, journals, and prior research. While the adoption of e-money has surged, particularly for its convenience, security, and speed in digital transactions, challenges persist in remote parts of Indonesia where cash remains prevalent. Recognizing this, Bank Indonesia collaborates with institutions to promote non-cash transactions, striving towards a cashless society.